STREET-LEVEL BUREAUCRACY DAN KETIMPANGAN AKSES ELPIJI BERSUBSIDI DI SINTANG - Markus Markus (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
This study examines the implementation of Indonesia's 3 kg subsidized LPG policy and the mechanisms producing localized access inequality. Utilizing a qualitative case study approach, data were gathered through in-depth interviews and field observations with street-level actors—agents, distributors, retailers—and low-income households. Findings reveal a significant implementation gap, where formal policy objectives are subverted by the discretionary practices of frontline bureaucrats. Operating within conditions of chronic supply scarcity, weak oversight, and complex social pressures, these actors enact selective distribution, personalize access, and set prices above official rates. Consequently, access is determined not by formal eligibility but by an individual's social capital, personal networks, economic means, geographic location, and bureaucratic literacy. The analysis demonstrates that inequality is not a passive outcome but is actively produced and normalized through these everyday administrative practices. This systematically excludes the most vulnerable, often forcing them back to traditional fuels. Thus, the subsidy is transformed from a tool for social justice into an arena for negotiating and entrenching local power relations. The study concludes that the policy's failure is socio-political, rooted in micro-level implementation politics that reinforce the very disparities the policy aims to reduce. Effective reform therefore requires moving beyond technical fixes to strengthen local governance, curtail arbitrary discretion, and foster inclusive oversight and community participation to ensure equitable distribution.